Coordinated optimal scheduling of island microgrid for power-hydrogen-carbon integration based on SAO-NSGA-II algorithm - XI Honglei; SUN Jingliao; QU Hezuo; SHI Zhengchai; HU Changhong; LIU Jinyuan (Zhejiang dianli, 2025)
In response to the high curtailment rate of solar energy and the frequent startup and shutoff operations of diesel generators， which lead to high carbon emissions in island microgrids， this paper proposes a coordinated optimal scheduling strategy for power-hydrogen-carbon integration based on the snow avalanche optimization-based non-dominated sorting genetic algorithm II （SAO-NSGA-II）. First， a multi-objective coordinated optimal scheduling model for power-hydrogen-carbon integration in island microgrids is established， taking into account the electrolytic hydrogen production system and carbon trading mechanisms. Then， SAO is used to improve NSGA-II， with different individual update formulas applied at different iteration stages to avoid local optima while maintaining the algorithm’s iteration speed. Finally， through simulation examples， a comparative analysis of the results before and after the algorithm improvement is performed， validating the feasibility of the proposed improved algorithm and optimal scheduling model. The improved algorithm demonstrates enhanced global search capability and better convergence results. The proposed optimal strategy achieves a coordinated optimization of the island microgrid， balancing economic efficiency and carbon emission costs， while also improving the utilization of the hydrogen energy system.